'The early bird catches the nest': possible competition between scops owls and ring‐necked parakeets. (21st January 2017) - Mori, E.; Ancillotto, L.; Menchetti, M.; Strubbe, D.
Abstract: Competition for critical resources is one of the key mechanisms through which invasive species impact on native communities. Among birds, the widely introduced ring‐necked parakeet Psittacula krameri locally affects cavity‐nesting communities through competition for suitable tree cavities, although it remains unclear to what extent such competition translates into population declines of native species. Here, we studied the potential for nest site competition between ring‐necked parakeets and the native scops owl Otus scops, a small nocturnal migratory raptor, by comparing the spatial distribution of the nest site locations of the raptor before (2002) and after (2015) the parakeet invasion. Pre‐invasion nesting sites of scops owls (2002) strongly coincided with those selected by ring‐necked parakeets, but although both parakeet and scops owl populations increased during the study period, this was no longer true for 2015. Ring‐necked parakeets took over several cavities formerly occupied by scops owls, and land‐use data suggest that because of the higher overall breeding densities in 2015, scops owls were forced to occupy suboptimal breeding habitats to minimize nest site competition with invasive parakeets. Ring‐necked parakeets start breeding early in the season, a behaviour enabling them to secure the best nest sites first, before the owls return from their wintering grounds. Our study highlights that locally observed competition not necessarily impacts on population dynamics of competing species and thus warns against uncritical extrapolation of smaller scale studies for assessing invasive species risks at larger spatial scales. Nonetheless, given the increasing number of studies demonstrating its competitive capacities, monitoring of ring‐necked parakeet populations is prudent and mitigation measures (such as mounting of man‐made nest‐boxes, which are used by scops owls, but not by parakeets) may be justified when the parakeets are likely to invade areas harbouring cavity‐nesters of conservation concern. Abstract : Before the invasion of ring‐necked parakeets, scops owls occupied a number of breeding sites located within urban parks and green areas within the city of Follonica (Southern Tuscany). After the invasion, ring‐necked parakeets took over several cavities formerly occupied by owls, forcing them to breed in suboptimal areas to avoid competition with alien parrots. Locally observed competition may occur without affecting population size of native species.